2023
DOI: 10.3390/ijerph20075320
|View full text |Cite
|
Sign up to set email alerts
|

Association between Malnutrition Assessed by the Global Leadership Initiative on Malnutrition Criteria and Mortality in Older People: A Scoping Review

Abstract: The Global Leadership Initiative on Malnutrition (GLIM) criteria were introduced in 2018 for the diagnosis of malnutrition in adults. This review was aimed at gathering the evidence about the association between malnutrition according to the GLIM criteria and mortality in older people, an emerging and clinically meaningful topic in the implementation of the GLIM criteria in geriatric healthcare settings. This scoping review considered meta-analyses, systematic reviews, cohort studies, and cross-sectional studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
(149 reference statements)
1
3
0
Order By: Relevance
“…The skeletal muscle mass index (SMI) serves as a key indicator in evaluating the nutritional status of patients, with low skeletal muscle mass commonly identi ed as sarcopenia. 13,14 The present study found that patients with sarcopenia exhibited signi cantly lower OS rates compared to those without sarcopenia, suggesting sarcopenia as a negative prognostic factor for individuals with laNPC. The underlying reasons for this association may be multifactorial.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The skeletal muscle mass index (SMI) serves as a key indicator in evaluating the nutritional status of patients, with low skeletal muscle mass commonly identi ed as sarcopenia. 13,14 The present study found that patients with sarcopenia exhibited signi cantly lower OS rates compared to those without sarcopenia, suggesting sarcopenia as a negative prognostic factor for individuals with laNPC. The underlying reasons for this association may be multifactorial.…”
Section: Discussionsupporting
confidence: 47%
“…The Skeletal Muscle Mass Index (SMI) serve as key indicators for evaluating patients' nutritional statuses. 13 Within the Global Leadership Initiative on Malnutrition (GLIM) consensus, low skeletal muscle mass, known as sarcopenia, is a diagnostic criterion for malnutrition in hospitalized patients. 14 The SMI is typically calculated by evaluating the cross-sectional area of skeletal muscle tissue at the third lumbar vertebra (L3) in abdominal images and dividing by the square of height (cm2/m2).…”
Section: Introductionmentioning
confidence: 99%
“…There are to date only a limited number of studies examining the contribution of the so-called phenotypic and etiologic factors used by GLIM to allcause mortality. 20,21 The objective of the current study was to assess the association between either risk of malnutrition (by NRS 2002) or malnutrition according to the diagnostic assessment of GLIM with all-cause mortality in hospitalized patients during a 2-year follow-up. Further, we wanted to investigate which of the phenotypic and etiologic criteria were associated with mortality in our population.…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulation treatment has been linked to lower all-cause mortality in community-dwelling older adults with atrial fibrillation, regardless of their health and functional condition ( Pilotto et al, 2016 ), showcasing the potential impact of therapeutic interventions on life expectancy. Malnutrition, evaluated by the Global Leadership Initiative on Malnutrition criteria, strongly correlates with mortality in both hospitalized and community-dwelling older individuals ( Sánchez-Rodríguez et al, 2023 ), underscoring the critical role of nutritional status. A decline in physical performance, as shown by finger tap reaction time, has been established as a risk factor for mortality and disability in older adults ( Shim et al, 2017 ), emphasizing the significance of assessing motor function in prognostic evaluations.…”
Section: Introductionmentioning
confidence: 99%